Dreaming, Mind-Wandering, and Hypnotic Dreams - Fazekas, Peter; Nemeth, Georgina (Frontiers in Neurology, 2020)
Hobson's AIM theory offers a general framework for thinking about states of consciousness like wakefulness, REM dreaming and NREM mentations in terms of a state space defined by the dimensions of the level of brain activity, the source of input, and the type of neurochemical modulation. This account inspired theoretical models of other altered states of consciousness—including hypnosis—claiming that studying REM dreaming can advance our understanding of these phenomena as well. However, recent developments showed that hypnosis is not a sleep like stage, and that the REM-centric attitude toward dreaming is mistaken. At the same time, the advancement of the neuro-cognitive theory claiming that dreaming and mind-wandering are on a continuum both underlain by default-mode network activity called many aspects of the AIM theory into question. Our aim in this paper is to show that certain hypnotic states—hypnotic dreams (experiences that subjects have in a hypnotic state as a result of an explicit suggestion to have a dream)—can, nevertheless, be highly relevant for the neuro-cognitive theory, and that their comparison with dreaming and mind-wandering has the potential to advance the field in unexpected ways.